Efektivitas Metode Pembelajaran Tutor Teman Sebaya untuk Meningkatkan Kemampuan Siswa Menganalisis Transaksi Keuangan Siswa - Noviani Putri; Rita Zahara; Euis Ani Arlinah (EDUCARE, 2012)
This research is motivated by the students' low ability to analyze financial transactions in Accounting learning. The objectives of this study are: To find out the effectiveness of the use of peer tutoring learning methods to improve financial transaction analysis skills and to determine the increase in the ability to analyze financial transactions after the Peer Tutor learning method has been conducted. The method used in this research is the experimental method. The population in this study were all students of class X SMK 3 Bandung. The sample in this study was class X AK 4 as an experimental class that received peer tutoring method learning and class X AK 3 as a control class that received ordinary learning. Based on the results of data calculation and hypothesis testing it can be concluded that the application of peer tutoring learning methods is more effective than ordinary learning and there is an increase in students' ability to analyze financial transactions after being given a peer tutoring method.